2022
DOI: 10.3390/foods11142165
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in Surface-Enhanced Raman Spectroscopy and Its Application in Food Analysis: Alcoholic Beverages as an Example

Abstract: Surface-enhanced Raman spectroscopy (SERS) is an emerging technology that combines Raman spectroscopy and nanotechnology with great potential. This technology can accurately characterize molecular adsorption behavior and molecular structure. Moreover, it can provide rapid and sensitive detection of molecules and trace substances. In practical application, SERS has the advantages of portability, no need for sample pretreatment, rapid analysis, high sensitivity, and ‘fingerprint’ recognition. Thus, it has great … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 185 publications
0
2
0
Order By: Relevance
“…We also successfully classified different brands of commercial liquors using PCA, and both Raman spectra and the closest group in the PCA diagram by ethanol standards of different concentrations can be used to determine the alcohol concentration. The data showed that the classification results were accurate, and this analysis method can be extended to other fields, such as food, 19 the environment, 20 and cellular discrimination, 21 and can even be combined with advanced SERS techniques for performing trace contaminant analysis.…”
Section: Discussionmentioning
confidence: 94%
“…We also successfully classified different brands of commercial liquors using PCA, and both Raman spectra and the closest group in the PCA diagram by ethanol standards of different concentrations can be used to determine the alcohol concentration. The data showed that the classification results were accurate, and this analysis method can be extended to other fields, such as food, 19 the environment, 20 and cellular discrimination, 21 and can even be combined with advanced SERS techniques for performing trace contaminant analysis.…”
Section: Discussionmentioning
confidence: 94%
“…Surface-enhanced Raman spectroscopy (SERS) is a technology in which the existence of metal nanoparticles can cause a plasma effect to enhance Raman spectrum signals. This technology was proved experimentally in 1977 [37]. C.V. Raman and K.S.…”
Section: Introductionmentioning
confidence: 95%
“…SERS is more specific and sensitive than Raman spectroscopy and can enhance the Raman signal of the molecule to be detected by 10 13 ~10 15 times. Therefore, SERS technology has a long-term application prospect in the detection of adulteration of Chinese herbal medicines [35], pesticide residues [36], and food safety testing [37].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, Raman spectroscopy (RS) has gained widespread recognition as a reliable and well-established technique for detecting and analyzing both organic and inorganic compounds in various fields, including food safety, archeology, medical diagnostics, and pharmaceuticals [1][2][3][4][5] due to its rapid, non-contact, and non-destructive approach. The analysis result of RS presents in the form of a Raman spectrum, which exhibits multiple peaks with varying positions and relative intensities.…”
Section: Introductionmentioning
confidence: 99%